Komunikasi Persuasif Antara Konselor dan ODHIV Dalam Pelayanan VCT di Puskesmas Dempo Palembang - Siti Munawaroh; Reza Aprianti; putri Citra Hati (Jurnal Prodi Ilmu Komunikasi, 2022)
This study entitled "Persuasive Communication Between Counselors and PLHIV in VCT Services at Puskesmas Dempo Palembang".Puskesmas Dempo is one of the health centers in the city of Palembang that provides VCT (Voluntary Counselling and Testing) services for people living with HIV. VCT (Voluntary Counselling and Testing) plays a role in the prevention and treatment of HIV/AIDS clients. VCT (Voluntary Counselling and Testing) activities are carried out to provide information and thoughts by a counselor to the counselee or patient to inform, change attitudes and exchange opinions for a better direction. The purpose of this research is to find out how the implementation of interpersonal communication that occurs between the counselor at Pusekesmas Dempo and PLHIV. And what obstacles are faced by counselors when counseling with patients. The research method used is descriptive qualitative. Sources of primary data by interviewing counselors and counselor assistants at Puskesmas Dempo Palembang and four people living with HIV (PLHIV). Secondary data sources are in the form of documents from the Dempo Palembang Health Center, books, journals, photos, and voice recordings. The theory used is the theory of social penetration where there is a process of openness and intimacy of a person in establishing relationships with other people through certain stages. The result of this study is that the communication that occurs between the counselor and PLWV goes well and effectively where the patient feels comfortable to share information about himself, take medication, and counsel regularly. And counselors also provide encouragement and motivation for the development of patients who are detected with HIV so that they do not give up in living life and can change their lifestyle towards a healthier one.